Association of Genetic Variants With Body-Mass Index and Blood Pressure in Adolescents: A Replication Study - Goulet, Danick; O’Loughlin, Jennifer; Sylvestre, Marie-Pierre (Frontiers in Genetics, 2021)
The strong correlation between adiposity and blood pressure might be explained in part by shared genetic risk factors. A recent study identified three nucleotide variants (rs16933812 (PAX5), rs7638110 (MRPS22), rs9930333 (FTO)) associated with both body mass index and systolic blood pressure in adolescents age 12 to 18 years. We attempted to replicate these findings in a sample of adolescents of similar age. A total of 713 adolescents were genotyped and had anthropometric indicators and blood pressure measured at age 13, 15, 17 and 24 years. Using linear mixed models, we assessed associations of these variants with body mass index and systolic blood pressure. In our data, rs9930333 (FTO) was associated with body mass index, but not systolic blood pressure. Neither rs16933812 (PAX5) nor rs7638110 (MRPS22) were associated with body mass index or systolic blood pressure. Although differences in phenotypic definitions and in genetic architecture across populations may explain some of the discrepancy across studies, nucleotide variant selection in the initial study may have led to false-positive results that could not be replicated.